Epigenetic Input Dictates the Threshold of Targeting of the Integrin-Dependent Pathway in Non-small Cell Lung Cancer - Zhang, Yang; Cheng, Kai; Xu, Bingwei; Shi, Junfeng; Qiang, Jun; Shi, Shujin; Yi, Yuanqin; Li, Hongxia; Jin, Tengchuan; Guo, Ruihua; Wu, Yadi; Liu, Zeyi; et al. (Frontiers in Cell and Developmental Biology, 2020)
We investigated the therapeutic potential of targeting integrin/FAK-dependent signaling, an adhesion receptor-mediated pathway that has been increasingly linked to non-small cell lung cancer (NSCLC) malignancy. Our analysis of the TCGA cohort showed that a subset of pro-tumorigenic integrins, including α1β1, α2β1, α3β1, α5β1, and α6β4, were frequently amplified or upregulated at the genomic or mRNA level in KRAS or EGFR mutation/overexpression-enriched adenocarcinomas. These alterations appeared complementary, correlated with poor patient survival (p < 0.0072), and were collaborative with KRAS mutation-coupled αv integrins (p < 0.00159). Since integrin/FAK-dependent signaling is tightly coupled with normal human physiology, we sought to use a synthetic lethal-type targeting comprising of VS-6063, a chemical inhibitor of integrin-mediated FAK activity, and A549 cells, which carry a KRAS mutation and EGFR overexpression. Our screening analysis revealed that JQ1 and IBET-762, inhibitors of epigenetic reader BRD4, and LBH589, a pan inhibitor of histone deacetylases (HDACs), exhibited synergy with VS-6063 in mitigating tumor cell viability. This epigenetic link was corroborated by strong effects of additional inhibitors and RNAi-mediated knockdown of FAK and BRD4 or its downstream effector, c-Myc. Low doses of JQ1 (≤0.5 μM) markedly escalated efficacy of VS-6063 across a panel of 10 NSCLC cell lines. This catalyst-like effect is in line with the oncogenic landscape in the TCGA cohort since c-Myc falls downstream of the KRAS and EGFR oncogenes. Mechanistically, co-inhibiting the integrin-FAK and BRD4/c-Myc axes synergistically induced apoptotic cell death and DNA damage response, and impaired stemness-associated tumorsphere formation. These effects were accompanied by a marked inhibition of Akt- and p130Cas/Src-dependent signaling, but not Erk1/2 activity. Meanwhile, JQ1 alone or in combination with VS-6063 attenuated cell-cell adhesion and extracellular matrix (ECM)-dependent cell spreading, which is reminiscent of phenotype induced by malfunctional E-cadherin or integrins. Paradoxically, this phenotypic impact coincided with downregulation of epithelial-mesenchymal transition (EMT)-inducting transcription factor ZEB1 or Snail. Finally, we showed that the effect of the VS-6063/JQ1 combination was nearly equivalent to that of VS-6063 plus Carboplatin or Osimertinib. Overall, our study indicates that the integrin/FAK and BRD4/c-Myc axes cooperatively drive NSCLC virulence, and a co-targeting may provide a line of therapy capable of overcoming EGFR/KRAS-driven malignancy.